Do newly founded firms pay lower wages? First evidence from Germany - Claus Schnabel; Susanne Kohaut; Udo Brixy (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2004)
Using a linked employer-employee data set for Germany, this paper analyses wage setting in a cohort of newly founded and other establishments from 1997 to 2001. While theory provides alternative explanations for higher or lower wages in newly founded firms, we show empirically that start-ups tend to pay lower wages, ceteris paribus. On average, wages in newly founded establishments are 8 percent lower than in similar incumbent firms. This negative wage differential is substantially smaller in eastern than in western Germany. The wage differential is shown to decline over time as the newly founded firms become more mature. – – Unter Verwendung eines kombinierten Firmen-Beschäftigten- Datensatzes für Deutschland analysiert dieser Beitrag die Lohnsetzung in einer Kohorte von neu gegründeten und anderen Betrieben im Zeitraum von 1997 bis 2001. Während theoretische Erklärungsansätze verschiedene Begründungen für höhere oder niedrigere Löhne in neu gegründeten Betrieben liefern, zeigen wir empirisch, dass Neugründungen ceteris paribus tendenziell niedrigere Löhne zahlen. Im Durchschnitt liegen die Löhne in Neugründungen 8 Prozent unter denen in vergleichbaren bestehenden Betrieben. Dieses negative Lohndifferenzial fällt in Ostdeutschland deutlich geringer aus als in Westdeutschland. Es zeigt sich, dass mit der Reifung der Betriebe im Zeitablauf das Lohndifferenzial zurückgeht.
Keywords: D21; J30; 330; Wages; newly founded firms; linked employer-employee data; Germany; Unternehmensgründung; Lohn; Lohnstruktur; Unternehmensentwicklung; Schätzung; Deutschland